The ReInvigorate Study—phrenic nerve-to-diaphragm stimulation for weaning from mechanical ventilation: a protocol for a randomized pivotal clinical trial - Katie Schaaf; Christopher M. Mullin; Kyle W. Cunningham; Jonathan Eaton; Steven A. Conrad (Trials, 2024)
Abstract Background In the United States in 2017, there were an estimated 903,745 hospitalizations involving mechanical ventilation (MV). Complications from ventilation can result in longer hospital stays, increased risk of disability, and increased healthcare costs. It has been hypothesized that electrically pacing the diaphragm by phrenic nerve stimulation during mechanical ventilation may minimize or reverse diaphragm dysfunction, resulting in faster weaning. Methods The ReInvigorate Trial is a prospective, multicenter, randomized, controlled clinical trial evaluating the safety and efficacy of Stimdia’s pdSTIM System for facilitating weaning from MV. The pdSTIM system employs percutaneously placed multipolar electrodes to stimulate the cervical phrenic nerves and activate contraction of the diaphragm bilaterally. Patients who were on mechanical ventilation for at least 96 h and who failed at least one weaning attempt were considered for enrollment in the study. The primary efficacy endpoint was the time to successful liberation from mechanical ventilation (treatment vs. control). Secondary endpoints will include the rapid shallow breathing index and other physiological and system characteristics. Safety will be summarized for both primary and additional analyses. All endpoints will be evaluated at 30 days or at the time of removal of mechanical ventilation, whichever is first. Discussion This pivotal study is being conducted under an investigational device exception with the U.S. Food and Drug Administration. The technology being studied could provide a first-of-kind therapy for difficult-to-wean patients on mechanical ventilation in an intensive care unit setting. Trial registration Clinicaltrials.gov, NCT05998018 , registered August 2023.